ESRA19-0205 Median nerve cross-sectional area and depth correlation with height, weight, BMI and mid-arm circumference. (30th August 2019) - Higginbotham, G; Gupta, P; Davies, P; Kumara, P
Abstract : Background and aims: The aim of this study was to ascertain the relationship between median nerve cross-sectional area (CSA) and depth from skin with height, weight, BMI and mid-arm circumference in healthy volunteers. Methods: After formal assessment from the Health Research Authority, UK, data was collected from 21 healthy volunteers (7 males, 14 females), median age 39 years (range 22–63). A SonoSite S-Nerve™ ultrasound machine was used to take an image of the median nerve at the mid-forearm using a 5–13MHz linear array probe. The inbuilt callipers were used to measure the nerve's CSA and depth. Height, weight, and mid-arm circumference was also recorded. The relationship between variables was evaluated using Spearman's rank correlation coefficient with STATA™ software. b) Annotated image: MN=median nerve, FDS=flexor digitorum superficialis, FCR=flexor carpi radialis, FDP= flexor digitorum profundus, FPL=flexor pollicis longus. Results: The mean median nerve CSA was 0.09 cm² (range 0.06–0.17). The correlation between nerve CSA and weight was positive and highly significant (rho=0.4132, p=0.0065). There was no significant correlation between CSA and BMI (rho=01524, p=0.3352) or mid-arm circumference (rho=0.232, p=0.1391). Median nerve depth showed statistically significant positive correlations with weight (rho=0.5814, p=0.0001), BMI (rho=0.7343, p=0.0000), and mid-arm circumference (rho=0.6855, p=0.0000). The correlation with height was not significant (rho=-0.0536, p=0.7362). Conclusions: This study suggests that median nerve CSA, which determines the dose of local anaesthetics [1], correlates strongly with weight. The depth of the nerve from the skin correlated most directly to the subject's BMI and mid-arm circumference.